Capital Gains Taxes and Equity Trading: Empirical Evidence - Blouin, Jennifer L.; Raedy, Jana Smith; Shackelford, Douglas A. (Journal of Accounting Research, 2003)
Abstract Individual investors have an incentive to defer selling appreciated stock until it qualifies for tax‐favored, long‐term capital gains treatment. Shackelford and Verrecchia [2002] show that these incentives can affect equity trading around public disclosures. This article provides some empirical support for their theory with evidence of price increases and equity constrictions around announcements of quarterly earnings and additions to the S&P 500 index. We find share returns rise and trading volume falls with the incremental taxes saved by deferring the sale of appreciated property. The price increases, however, are temporary, reversing in subsequent trading days. The results are consistent with buyers believing the compensation to sell before long‐term qualification (through higher prices) is less costly than holding an inappropriately weighted portfolio. This finding—that personal capital gains taxes affect equity trading—adds to a growing literature that challenges longstanding assumptions that firm value is independent of shareholders and their taxes.